Carbon-based nanomaterials and nanocomposites for gas sensing - Shimpi, Navinchandra Gopal (Micro and nano technologies, 2021)
Carbon-Based Nanomaterials and Nanocomposites for Gas Sensing discusses the state of the art, emerging challenges, properties, and opportunities of various carbon-based nanomaterials and nanocomposites, for their application in smart gas sensors. The book focuses on various carbon-based nanomaterials and their nanocomposites, sensing mechanism, device fabrication, and their application for the sensing of various hazardous gases. This is important for several industries, environmental monitoring, and human healthcare, due to increased industrialization. Carbon-Based Nanomaterials and Nanocomposites for Gas Sensing provides systematic and effective guidelines for researchers who want to gain a fundamental understanding of how this class of materials is being used for gas sensing. Since these sensors can be applied for the automation of numerous industrial processes, as well as for everyday monitoring of various activities, such as public safety, engine performance, medical therapeutics, and in many other situations, this book will catch the attention of readers and motivate them for advanced research in the development of smart and efficient gas sensors.